Comparative Analysis of the Istinbath Methods of the Shafi'i and Hanafi Schools Regarding the Role of the Wali Mujbir in Marriage Law - Asman, Asman (Al-Ahkam: Jurnal Ilmu Syari’ah dan Hukum, 2024)
This study provides an understanding of the differences in the istinbath methods of the Syafi'i and Hanafi schools regarding the determination of a mujbir guardian. The right of a mujbir guardian only applies to girls or widows who are still children because an adult woman is considered capable of determining her life partner without the need for the consent of a guardian. So that it can distinguish the methods of determining the law between the Syafi'i and Hanafi schools regarding the determination of a mujbir guardian. The focus of this study is the difference between the istinbath method of madzhab shafi'i and madhhab hanafi regarding wali mujbir. While the method in this study is qualitative research that is literary and the approach in this study uses a normative approach. The normative approach is an approach whose study is through the literacy of sources consisting of the Qur'an, hadith, Islamic fiqh books, books relevant to the discussion, Islamic law journals and other references related to wali mujbir. The result of this study is that in order to protect the human rights of women, this concept is not appropriate to use. Although in reality there are still many practices of the concept of wali mujbir in Indonesia, considering that madzab Shafi'i is the most followed madzab in Indonesia. But still, this is contrary to Law number 1 of 1974 which is listed in article 6 paragraph (1) chapter II.